Economic evaluation of crossbreeding for dairy production in a pasture based production system in Kenya - Kahi, A.K.; Thorpe, W.R.; Nitter, G.; Arendonk, Johan A.M. van; Gall, C.F. (Elsevier, 2000)
Data on accumulated life performance of crosses of Ayrshire (A), Brown Swiss (B), Friesian (F) and Sahiwal (S) cattle collected over a 21-year period from a dairy ranch in the lowland tropics of Kenya were analysed to estimate additive and non-additive genetic effects on economic traits. These were used to predict and compare, first, performance of cows under nine crossbreeding strategies and, second, the performance of the production systems when applying the strategies that included maintaining the purebred S dams and bulls required for the production of crossbreds. Performance was predicted from parameters of a genetic model based on additive-dominance and additive×additive interaction effects for the following strategies: first cross (F×S), two-breed rotation (AS)Rot, three-breed rotation (BFS)Rot and two- (F and S), three- (B, F and S) and four- (A, B, F and S) breed synthetic (Syn) breeds based on equal and unequal contributions of the foundation breeds. The sensitivity of predicted performance at the cow level to variation in economic parameters was also investigated. For profit per day of productive herdlife (PLD), the B and F additive breed effects were not significantly different from that of A. The additive breed effect for S was negative and significant (P<0.01) indicating that it was inferior to the Bos taurus for PLD. Dominance effects for PLD in the crosses A×S and B×S were positive and significant (P<0.05). The additive×additive interactions were negative and significant in all the crosses. At the individual cow level, predicted PLD would be lowest in (ABFS)Syn and highest in F×S. The (3/4F 1/4S)Syn would be the second-best strategy giving 90% of the expected F×S profit, while (FS)Syn would give 87%. At the production system level, systems based on F×S cows were superior to those based on the rotations at all level of number of calvings (NL) and would be superior to those based on the two-breed synthetics only at a NL higher than 4. Variation of costs and prices greatly affected predicted economic benefit but not the ranking of strategies. The absence of significant differences in the additive breed effects of the B. taurus breeds for PLD showed that comparable economic benefits were derived by use of any of the three breeds for continuous crossbreeding with the S in a production system with management achieving 3000 kg lactation yields. It is also expected that the economic benefits from the development of two-breed synthetic breeds based on A, B or F would also be comparable in production systems achieving lower yields (e.g., in many smallholder units).